(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
The work has done for environmental conservation, doing the right management of urban solid waste in the Echandia’s Municipality, from a socio-environmental approach with guidelines of the scientific method. Based on waste samples collected real information on the amount and type of waste generated was obtained, data obtained is: 48% of waste generated is plastics, paper and cardboard 38%, 10% glass and 4% metals, a second sampling data obtained confirm it. Organic waste is not present because it is used for animal breeding. The per-capita waste is 3.4 kg / inhabitant / day. The pilot plan reduces the volume of waste generated daily; environmental awareness was obtained with community training, so these products were used for recycling and generated revenue for Echandia Municipality.